Ultrasonic-assisted melt crystallization method
Through two-stage cooling and crystallization process and ultrasonic auxiliary technology, ultrasonic disturbances are used to promote cooling and nucleation of materials, reduce crystal impurities, improve product purity and crystallization efficiency, and solve the problems of difficulty in forming crystallization cores and low efficiency in the existing technology. It is suitable for multiple Chemical materials.
Patent Information
- Application Number
- CN202411753837.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing ultrasonic assisted melt crystallization methods still have room for improvement in improving product purity, especially in the formation of crystallization cores and efficiency improvement.
Using a two-stage cooling and crystallization process, the first stage cooling rate is greater than the second stage. At the beginning, ultrasonic assisted crystallization of 40-50kHz is enabled, and the ultrasonic frequency is reduced to 20-30kHz when the crystal appears, and the power is set to 60-80W, combined with Appropriate cooling amplitude and material selection of heat exchange media, and perform ultrasonic assisted melt crystallization.
Significantly shortens the nucleation time, improves product purity and cooling rate, enhances crystal integrity, improves crystallization efficiency and purity, and is suitable for a variety of materials such as vinyl carbonate and fluorovinyl carbonate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to an ultrasonic wave assisted melting crystallization method. Background Art
[0002] Melt crystallization is an important chemical separation technology with the advantages of low energy consumption, high efficiency, wide application range, environmental friendliness, and low-temperature operation. It is widely used in chemical, pharmaceutical, food and other industries. The basic principle of melt crystallization is to heat the raw material liquid at a temperature higher than its melting point to make it in a molten state, and then circulate the heat exchange medium in the cooling plate or tube bundle to gradually cool and crystallize the raw material liquid outside the plate, that is, separation is achieved through the different melting points of the components of the mixture. Melt crystallization can be divided into two stages: crystallization and sweating. In the crystallization stage, some components in the mixture are crystallized by controlling the temperature. The driving force of the crystallization process is saturation or supercooling. Due to the difference in melting points of the system to be separated, and the molecules with different shapes or sizes are not easy to enter the crystal lattice, the crystal phase produced by crystallization has a higher purity than the residual liquid. Sweating is a post-processing process to improve the purity of the crystal phase. In this stage, the temperature of the heat exchange medium is controlled to gradually heat the crystal layer. Because the impurities are unevenly distributed in the crystal layer, the melting point of some crystal layers containing higher impurities is low, and they will first melt into liquid and be discharged, and play a role in replacing and flushing the residual liquid attached to the crystal. The purity of the substance can be greatly improved through crystallization and sweating operations.
[0003] However, melt crystallization has the following defects: the formation of crystal cores is difficult, which not only prolongs the crystallization time but also reduces the crystallization efficiency. In traditional methods, seed crystals are usually added to promote nucleation and thus improve the crystallization efficiency. However, the seed crystal size and particle size distribution are difficult to control, and new impurities are easily introduced, resulting in reduced purity. There are also methods that use ultrasound to assist crystallization. For example, the patent document with publication number CN104402697A discloses a method for crystallization of coenzyme Q10 assisted by ultrasound. This scheme uses coenzyme Q 10The introduction of ultrasound during the crystallization process can effectively promote nucleation, reduce agglomeration, and improve the purity of the crystallized product. The theoretical basis is to use ultrasonic cavitation to assist crystallization. In a liquid, when the power of the sound wave is large enough and the negative pressure on the liquid is strong enough, the average distance between the molecules of the medium will increase and exceed the limit distance, thereby breaking the liquid to form a cavity. At the moment when the cavitated cavity shrinks and collapses violently, local high pressure and high temperature of thousands of degrees can be generated in the bubble, thus forming ultrasonic cavitation. It is generally believed that the rapid cooling process of ultrasonic cavitation will cause extremely high local supersaturation in the crystallization solution system, promoting the crystallization of the solution; the propagation of ultrasonic waves in the solution system medium can accelerate the effective collision and diffusion of solute molecules, effectively promoting the primary nucleation; the microjets generated by cavitation can cause effective impact on large crystal seeds, forming partial crushing and dissolution of large grains, effectively promoting secondary nucleation, promoting the formation of uniform small grains, solving the preparation of crystal seeds and increasing the number of crystal seeds, and improving the output of crystal growth and the crystallization yield. The mechanical effect, thermal effect and activation effect caused by ultrasonic cavitation can effectively improve the mass transfer and heat transfer effects of the solution, thereby promoting the crystallization process to obtain good crystals.
[0004] However, the purity of the product needs to be further improved by using ultrasonic assisted crystallization. Summary of the invention
[0005] In view of this, the present invention provides an ultrasonic assisted melt crystallization method to further improve the purity of the product.
[0006] To achieve the above solution, the technical solution of the present invention is as follows: The present invention provides an ultrasonic assisted melt crystallization method, which sequentially comprises a cooling crystallization process and a sweating process, wherein the cooling crystallization process comprises a first cooling stage and a second cooling stage, wherein the cooling rate of the first cooling stage is greater than the cooling rate of the second cooling stage, and ultrasonic waves are activated at the beginning of the first cooling stage or the beginning of the second cooling stage to assist the crystallization of a material to be purified, and the frequency of the ultrasonic waves is reduced when crystals begin to appear.
[0007] The present application enables the use of ultrasound to assist the crystallization of the material to be purified at the beginning of the first cooling stage or the beginning of the second cooling stage, and can utilize ultrasonic disturbance to promote the cooling and nucleation of the material, reduce impurities entrained in the crystal, shorten the nucleation time, increase the cooling rate, and improve the product purity. In addition, enabling ultrasound to assist crystallization during the crystallization process can accelerate melting, reduce melting temperature, and improve product purity. By reducing the frequency of the ultrasound when crystals begin to appear, the integrity of the crystals can be improved, thereby improving product purity.
[0008] Optionally, at the beginning of the first cooling stage or the beginning of the second cooling stage, ultrasound with a frequency of 40-50 kHz is activated to assist crystallization of the material to be purified.
[0009] Optionally, the frequency of the ultrasound is reduced to 20-30 kHz, preferably 25-30 kHz, when crystals begin to appear.
[0010] Specifically, the present application can further improve the integrity of the crystals and further improve the purity of the product by setting the frequency of the ultrasonic waves to be lowered to 20-25 kHz, especially 25-30 kHz, when crystals begin to appear.
[0011] Optionally, the power of the ultrasonic wave is 60-80W, preferably 70-80W.
[0012] Specifically, the present application sets the power of the ultrasonic wave to 60-80W, especially to 70-80W, which can reduce the strength of the crystal particles, increase the growth rate of the crystal nucleus, increase the cooling rate, and further improve the product purity.
[0013] Optionally, the material to be purified is selected from fluoroethylene carbonate or ethylene carbonate.
[0014] Optionally, the temperature reduction amplitude in the first temperature reduction stage is smaller than the temperature reduction amplitude in the second temperature reduction stage.
[0015] Optionally, the temperature reduction range of the heat exchange medium used in the first temperature reduction stage is 8-11°C, and the temperature reduction range of the heat exchange medium used in the second temperature reduction stage is 15-20°C.
[0016] Optionally, if the material to be purified is fluoroethylene carbonate, during the crystallization process, the heat exchange medium is an ethylene glycol aqueous solution.
[0017] Optionally, in the ethylene glycol aqueous solution, the concentration of ethylene glycol is 25wt%-35wt%.
[0018] Optionally, if the material to be purified is ethylene carbonate, during the crystallization process, the heat exchange medium is water.
[0019] Optionally, after sweating, the ultrasonic-assisted melt crystallization method further comprises: heating and melting. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] An embodiment of the present application provides an ultrasonic assisted melt crystallization method, which includes a cooling crystallization process, a sweating process and a heating melting process in sequence. The cooling crystallization process includes a first cooling stage and a second cooling stage. The cooling rate of the first cooling stage is greater than the cooling rate of the second cooling stage. At the beginning of the first cooling stage or the beginning of the second cooling stage, ultrasonic waves with a frequency of 40-50kHz and a power of 60-80W are used to assist the crystallization of the material to be purified, and when crystals begin to appear, the frequency of the ultrasonic waves is reduced to 20-30kHz. The material to be purified is selected from fluoroethylene carbonate or ethylene carbonate.
[0022] The cooling amplitude of the first cooling stage is smaller than that of the second cooling stage. The cooling amplitude of the heat exchange medium used in the first cooling stage is 8-11°C, and the cooling amplitude of the heat exchange medium used in the second cooling stage is 15-20°C. If the material to be purified is fluoroethylene carbonate, the heat exchange medium during the crystallization process is ethylene glycol aqueous solution; if the material to be purified is ethylene carbonate, the heat exchange medium during the crystallization process is water.
[0023] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0024] Example 1 The melt crystallization method of ethylene carbonate (EC for short) has the following specific steps: The molten ethylene carbonate to be crystallized (purity of 95.00wt%, tested in accordance with HG / T 5391-2018 Industrial Ethylene Carbonate) is fed into a static crystallizer; Heat exchange medium water is introduced into the crystallizer through the heat exchange medium inlet for cooling crystallization. During the cooling crystallization process, the temperature of the heat exchange medium is rapidly cooled from 43°C to 32°C (i.e., the first cooling stage, with a cooling rate of 0.278°C / min). At this time, the ultrasonic generator is turned on to assist crystallization. The ultrasonic frequency is 40kHz and the ultrasonic power is 80W. Then, the temperature of the heat exchange medium was slowly cooled from 32°C to 16°C (i.e., the second cooling stage, with a cooling rate of 0.079°C / min) until the crystal nucleation was completed. After the temperature was kept constant for 0.2h, the crystallization was completed and the power supply of the ultrasonic generator was turned off. When crystallization begins to occur during the cooling crystallization process, the frequency of ultrasound is adjusted to 30 kHz; After the cooling crystallization is completed, sweating is carried out, and the temperature is raised to the final temperature of the sweating material 37°C to discharge sweat; After the sweating process is completed, the temperature is raised to melt, the heat exchange medium is heated to 43°C, the material is completely melted, the obtained product is discharged from the crystallizer material outlet, collected, weighed and sampled, and the product purity is tested in accordance with "HG / T 5391-2018 Industrial Ethylene Carbonate". The results are shown in Table 1.
[0025] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0026] Example 2 The difference between this embodiment and embodiment 1 is that the frequency of ultrasound is adjusted to 20 kHz when crystallization begins to occur during the cooling crystallization process.
[0027] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0028] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0029] Example 3 The melt crystallization method of fluoroethylene carbonate (FEC) has the following specific steps: The molten fluoroethylene carbonate to be crystallized (purity of 95wt%, tested in accordance with HG / T 4790-2014 Fluoroethylene Carbonate) is fed into a static crystallizer; An aqueous solution of ethylene glycol (the concentration of ethylene glycol is 30wt%) is introduced into the crystallizer through the heat exchange medium inlet for cooling crystallization. During the cooling crystallization process, the temperature of the heat exchange medium is rapidly cooled from 28°C to 20°C (i.e., the first cooling stage, with a cooling rate of 0.277°C / min). At this time, an ultrasonic generator is turned on to assist crystallization. The frequency of the ultrasound is 40kHz, and the power of the ultrasound is 80W. Next, the temperature of the heat exchange medium is slowly cooled from 20°C to 5°C (i.e., the second cooling stage, with a cooling rate of 0.080°C / min) until the crystal nucleation is completed. After the temperature is kept constant for 0.2h, the crystallization is completed, and the power supply of the ultrasonic generator is turned off. When crystallization begins to occur during the cooling crystallization process, the frequency of ultrasound is adjusted to 30 kHz; After the cooling crystallization is completed, sweating is carried out, and the temperature is raised to the final temperature of the sweating material 37°C to discharge sweat; After the sweating process is completed, the temperature is raised and melted, and the obtained product is discharged from the material outlet of the crystallizer and collected, weighed and sampled, and the product purity is tested in accordance with "HG / T 4790-2014 Fluoroethylene Carbonate". The results are shown in Table 1.
[0030] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0031] Comparative Example 1 The difference between this comparative example and Example 1 is that the ultrasonic generator is turned on at the beginning of the second cooling stage to assist crystallization, the ultrasonic frequency is 40 kHz, the ultrasonic power is 80 W, and the ultrasonic frequency is not adjusted during the cooling crystallization process.
[0032] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0033] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0034] Comparative Example 2 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the frequency of the ultrasound is 30 kHz, and the power of the ultrasound is 80 W.
[0035] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0036] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0037] Comparative Example 3 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the ultrasonic frequency is 50 kHz, and the ultrasonic power is 80 W.
[0038] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0039] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0040] Comparative Example 4 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the frequency of the ultrasound is 40 kHz, and the power of the ultrasound is 60 W.
[0041] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0042] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0043] Comparative Example 5 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the ultrasonic frequency is 40 kHz, and the ultrasonic power is 70 W.
[0044] The purity of ethylene carbonate in the product was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”. The results are shown in Table 1.
[0045] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0046] Comparative Example 6 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the frequency of the ultrasound is 40 kHz, and the power of the ultrasound is 90 W.
[0047] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0048] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0049] Comparative Example 7 The difference between this comparative example and Example 1 is that ultrasound is not used.
[0050] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0051] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0052] Comparative Example 8 The difference between this comparative example and comparative example 1 is that at the beginning of the first cooling stage, an ultrasonic generator is turned on to assist crystallization, the frequency of the ultrasound is 40 kHz, and the power of the ultrasound is 80 W.
[0053] The product purity was tested in accordance with “HG / T 5391-2018 Industrial Ethylene Carbonate”, and the results are shown in Table 1.
[0054] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0055] Comparative Example 9 The difference between this comparative example and Example 3 is that the frequency of ultrasound is not adjusted during the cooling crystallization process.
[0056] The product purity was tested according to "HG / T 4790-2014 Fluoroethylene Carbonate", and the results are shown in Table 1.
[0057] The crystallization endpoint temperature and melting endpoint temperature of the material were detected, and the results are shown in Table 1.
[0058] Table 1 Test results
[0059] As shown in Table 1, compared with Comparative Example 7 (no ultrasound), Comparative Example 8 (ultrasound assisted crystallization at the beginning of the first cooling stage) and Comparative Example 1 (ultrasound assisted crystallization at the beginning of the second cooling stage) have significantly lower melting temperatures and significantly improved product purity. This result shows that by enabling ultrasound to assist crystallization during the crystallization process, the present application can utilize wave disturbance to promote material cooling and nucleation, reduce impurities entrained in the crystal, significantly shorten the nucleation time, increase the cooling rate, and thus improve product purity; and enabling ultrasound to assist crystallization during the crystallization process can accelerate melting, reduce melting temperature, and improve product purity.
[0060] From Comparative Example 8 (ultrasonic frequency is 40kHz, ultrasonic power is 80W) and Comparative Examples 4-6 (ultrasonic frequency is 40kHz, ultrasonic power is 60W, 70W and 90W respectively) in Table 1, it can be seen that with the increase of ultrasonic power, the purity of the product shows an upward trend, but after the ultrasonic power increases to 80W, the product purity does not change significantly when the ultrasonic power continues to increase. The results show that with the increase of ultrasonic power, the particle size of the crystal particles gradually decreases, the growth rate of the crystal nucleus gradually increases, and the cooling rate significantly increases, thereby improving the purity of the product; when the ultrasonic power is greater than 80W, the effect on crystal growth is not obvious, and a growth plateau period appears.
[0061] From Comparative Example 2 (ultrasonic frequency of 30kHz), Comparative Example 3 (ultrasonic frequency of 50kHz) and Comparative Example 8 (ultrasonic frequency of 40kHz) in Table 1, it can be seen that with the increase of ultrasonic frequency, the purity of the product shows an upward trend, and the product purity is the highest when the operating frequency is 40kHZ. If the ultrasonic frequency is further increased, the product purity will decrease instead of increase. This result shows that too high ultrasonic frequency will cause excessive crystal disturbance and incomplete nucleation, and too low ultrasonic frequency will cause impurities to be wrapped on the crystal and difficult to remove, which will reduce the purity of the product.
[0062] As shown in Table 1, compared with Comparative Example 2 (the ultrasonic frequency was not adjusted during the cooling crystallization process), the purity of the products of Example 1 (the ultrasonic frequency was adjusted to 30kHz when crystallization began to appear during the cooling crystallization process) and Example 2 (the ultrasonic frequency was adjusted to 20kHz when crystallization began to appear during the cooling crystallization process) increased significantly, and compared with Example 2 (the ultrasonic frequency was adjusted to 20kHz when crystallization began to appear during the cooling crystallization process), the purity of the product of Example 1 (the ultrasonic frequency was adjusted to 30kHz when crystallization began to appear during the cooling crystallization process) increased significantly. The results show that lowering the ultrasonic frequency when crystallization begins can better protect the integrity of the crystal and improve the purity of the product. Too high ultrasonic frequency will cause too much disturbance or too low ultrasonic frequency will wrap impurities, which will lead to a decrease in product purity. And compared with Example 3 and Comparative Example 9, lowering the frequency during the cooling crystallization process can improve the purity of fluoroethylene carbonate. The results show that the method of the present application is not only applicable to the melt crystallization of ethylene carbonate, but also to the melt crystallization of fluoroethylene carbonate, and the method has a wide range of applications.
[0063] In summary, the present application uses ultrasonic wave to assist crystallization during the crystallization process, and can use wave disturbance to promote material cooling and nucleation, reduce impurities entrained in the crystal, significantly shorten the nucleation time, increase the cooling rate, and thus improve the product purity. With the increase of ultrasonic power, the particle size of the crystal particles gradually decreases, the growth rate of the crystal nucleus gradually increases, and the cooling rate is significantly improved, thereby improving the product purity; when the power is greater than 80W, the effect on crystal growth is not obvious, and a growth plateau occurs. Too high an ultrasonic frequency will cause excessive crystal disturbance and incomplete nucleation. If the ultrasonic frequency is too low, impurities will be wrapped on the crystal and difficult to remove, which will reduce the product purity. Lowering the ultrasonic frequency when crystallization begins to occur can better protect the integrity of the crystal and improve the product purity. Too high an ultrasonic frequency will cause excessive disturbance or too low an ultrasonic frequency will cause impurities to be wrapped, which will lead to a reduction in product purity. This method is applicable to a variety of materials.
[0064] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An ultrasonic assisted melt crystallization method, the ultrasonic assisted melt crystallization method sequentially comprises a cooling crystallization process and a sweating process, the cooling crystallization process comprises a first cooling stage and a second cooling stage, the cooling rate of the first cooling stage is greater than the cooling rate of the second cooling stage, characterized in that: At the beginning of the first cooling stage or the second cooling stage, ultrasound is activated to assist crystallization of the material to be purified, and the frequency of the ultrasound is reduced when crystals begin to appear.
2. The ultrasonic assisted melt crystallization method according to claim 1, characterized in that: At the beginning of the first cooling stage or the second cooling stage, ultrasound with a frequency of 40-50 kHz is used to assist crystallization of the material to be purified.
3. The ultrasonic assisted melt crystallization method according to claim 2, characterized in that: When crystals begin to appear the frequency of the ultrasound is reduced to 20-30 kHz.
4. The ultrasonic assisted melt crystallization method according to claim 1, characterized in that: The power of the ultrasonic wave is 60-80W.
5. The ultrasonic assisted melt crystallization method according to claim 1, characterized in that: The material to be purified is selected from fluoroethylene carbonate or ethylene carbonate.
6. The ultrasonic assisted melt crystallization method according to claim 5, characterized in that: The temperature reduction range in the first temperature reduction stage is smaller than the temperature reduction range in the second temperature reduction stage.
7. The ultrasonic assisted melt crystallization method according to claim 6, characterized in that: The temperature reduction range of the heat exchange medium used in the first temperature reduction stage is 8-11°C, and the temperature reduction range of the heat exchange medium used in the second temperature reduction stage is 15-20°C.
8. The ultrasonic assisted melt crystallization method according to claim 7, characterized in that: If the material to be purified is fluoroethylene carbonate, during the crystallization process, the heat exchange medium is an ethylene glycol aqueous solution.
9. The ultrasonic assisted melt crystallization method according to claim 7, characterized in that: If the material to be purified is ethylene carbonate, during the crystallization process, the heat exchange medium is water.
10. The ultrasonic assisted melt crystallization method according to claim 1, characterized in that: After sweating, the ultrasonic-assisted melt crystallization method further comprises: heating and melting.
Citation Information
Patent Citations
Ultrasonic-assisted coenzyme Q10 crystallizing method
CN104402697A
BE673693A
Apparatus of ultrasound heat exchange
CN101091838A
Method for purifying vinylene carbonate
CN101195610A
Supersonic wave method for promoting rapid crystallization and fractionation of palm oil
CN102229860A